THU0028 Fibroblast-like synoviocytes inhibit TNF- and RANKL-induced human osteoclast precursor differentiation following exposure to IL-1BETA. (23rd January 2014) - Harvey, B.P.; Syed, F.; Kaymakcalan, Z.
Abstract : Background: Inflammatory cytokines such as TNF-alpha (TNF), IL-1beta (IL-1b) and IL-6 have been shown to contribute to osteoclastogenesis independently or in conjunction with M-CSF or RANKL, two key cytokines involved in osteoclast development. However, the role of TNF as well as the other inflammatory cytokines in promoting the expression of these key osteoclastogenic factors in synovial tissue and the concomitant induction of osteoclast differentiation is poorly understood. Objectives: The objective of this study was to determine whether TNF, IL-1b or IL-6, separately or in combination, could induce human osteoclast differentiation and activity directly in the absence or presence of fibroblast-like synoviocytes (FLS). Methods: FLS from rheumatoid arthritis (RA) donors were pre-treated with various combinations of TNF, IL-1b, IL-6, soluble IL-6 receptor (sIL-6R), M-CSF and RANKL for 24 hr with or without osteoprotegerin (OPG). Human osteoclast precursors (OCP) were then co-cultured with the FLS, or cultured alone for 7 days. RANKL expression in FLS was evaluated by Western blot. Osteoclast differentiation was determined by the presence of large multinucleated cells positive for tartrate-resistant acid phosphatase (TRAP) and by TRAP5b activity. Resorptive activity was measured by the release of cross-linked C-telopeptide of type I collagen (CTX-I) from human bone chips. Results: Both TNF and IL-1b were able to induce RANKL expression in RA-FLS. Treatment of RA-FLS and OCP with a combination of TNF and M-CSF led to the appearance of TRAP+ multinucleated cells and an increase in TRAP5b activity; whereas, the combination of TNF and RANKL was ineffective in inducing osteoclasts, suggesting that TNF could substitute for exogenous RANKL but not M-CSF. Addition of the RANKL inhibitor OPG caused a significant reduction in TRAP+ multinucleated cells without altering the level of TRAP5b activity. A greater degree of inhibition was observed with the addition of IL-1b alone or in combination with IL-6 and sIL-6R, since the generation of both TRAP+ multinucleated cells and TRAP5b were significantly reduced even in the presence of exogenous RANKL. Addition of TNF to cultures with exogenous RANKL failed to overcome IL-1b-mediated inhibition of osteoclast differentiation; however, TNF did promote earlier differentiation (increased TRAcP5b activity by day 4) and enhanced activity of the osteoclasts (increased CTX-I levels by day 7) as compared to RANKL alone. Interestingly, the inhibitory effect of IL-1b was only observed in the presence of RA-FLS. Conclusions: These findings suggest that in a co-culture of RA-FLS and OCP, TNF can induce an early stage of osteoclast generation independent of RANKL as indicated by the expression of TRAP5b in the presence of OPG. However, later stages of differentiation into multinucleated cells requires TNF-induced RANKL expression from the FLS since the number of TRAP+ multinucleated cells was reduced with OPG treatment. Surprisingly, IL-1b prevented both the expression of TRAP5b and the generation of CTX-I that was induced by either TNF or RANKL but only in the presence of RA-FLS, suggesting that this pro-inflammatory cytokine can inhibit osteoclast development at an early stage by promoting the secretion of a putative inhibitory factor from the FLS. Disclosure of Interest: B. Harvey Shareholder of: Abbott Laboratories, Employee of: Abbott Laboratories, F. Syed Shareholder of: Abbott Laboratories, Employee of: Abbott Laboratories, Z. Kaymakcalan Shareholder of: Abbott Laboratories, Employee of: Abbott Laboratories